Modern compiler design - Grune, Dick.; Bal, Henr E.; Jacobs, Ceriel J. H.; Langendoen, Koen G. (J. Wiley, 2000)
This book is divided into nine parts: Introduction; From program text to abstract syntax tree; Annotating the abstract syntax tree-the context; Processing the intermediate code; Memory management; Imperative and object-oriented programs; Functional programs; Logic programs; and Parallel and distributed programs.